Answer:
C. x ≤ -1 or x > 4
Step-by-step explanation:
We need to solve both inequalities. For the first one, we get:
3 - 2x ≥ 5
Subtract 3 from both sides:
3 - 2x - 3 ≥ 5 - 3
-2x ≥ 2
Divide both sides by -2. Since -2 is negative the sign will change, so:
-2x/(-2) ≤ 2/(-2)
x ≤ -1
Now, we can solve the second inequality, so:
3(x - 2) + 1 > 7
Apply the distributive property:
3x - 3(2) + 1 > 7
3x - 6 + 1 > 7
3x - 5 > 7
Add 5 to both sides:
3x - 5 + 5 > 7 + 5
3x > 12
Finally, divide by 3:
3x/3 > 12/3
x > 4
Therefore, the solution of the compound inequality is:
C. x ≤ -1 or x > 4